2016
DOI: 10.21608/ijci.2016.33955
|View full text |Cite
|
Sign up to set email alerts
|

Semantic-based Approach for Solving the Heterogeneity of Clinical Data

Abstract: Clinical records contain massive heterogeneity number of data types, generally written in free-note without a linguistic standard. Other forms of medical data include medical images with/without metadata (e.g., CT, MRI, radiology, etc.), audios (e.g., transcriptions, ultrasound), videos (e.g., surgery recording), and structured data (e.g., laboratory test results, age, year, weight, billing, etc.). Consequently, to retrieve the knowledge from these data is not trivial task. Handling the heterogeneity besides l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Study results demonstrated that the proposed framework is significantly more accurate and faster than existing methods. [ 152 ]…”
Section: Challenging Issues Faced With Ai and Microfluidics For Biote...mentioning
confidence: 99%
“…Study results demonstrated that the proposed framework is significantly more accurate and faster than existing methods. [ 152 ]…”
Section: Challenging Issues Faced With Ai and Microfluidics For Biote...mentioning
confidence: 99%
“…Additionally, Elsharkawy, Ahmed, and Salem [42] believe that the heterogeneity and complexity are two main issues highlighted for the solution and integration of clinical data. The data are generated in different formats, such as RDF, XML, and images.…”
Section: Which Of the Domains Are Mainly Focused On Researching Heterogeneity?mentioning
confidence: 99%
“…Data can exist over numerous datasets, which requires data to be consolidated and merged using some common fields [ 12 ]. Data integration can be defined as the process of integrating data from various sources in a standard format, storing data in proper repositories, and providing a unified view of the data to be used for retrieval and analysis [ 60 ].…”
Section: Semantics For Healthcare Data Integrationmentioning
confidence: 99%